Urlaub vom Frieden . Vacation from Peace - Hak-Hagir, Amin (Luland, 2008)
Verzio FF Submission During the Balkan War, Austrian soldiers leave the neutrality of their country to go to war as mercenaries. Director Amin Hak-Hagir lets one of them, who fought for Croatia, speak in front of the camera. In a deserted house and dressed for combat, the ex-mercenary describes how professional adventure - and the death of comrades - became routine. In the course of his narrative, the price that the well-paid war work cost him also comes to light.